Drivers of Bacterial α- and β-Diversity Patterns and Functioning in Subsurface Hadal Sediments - Rastelli, Eugenio; Corinaldesi, Cinzia; Dell’Anno, Antonio; Tangherlini, Michael; Lo Martire, Marco; Nishizawa, Manabu; Nomaki, Hidetaka; Nunoura, Takuro; Danovaro, Roberto (Frontiers in Microbiology, 2019)
Oceanic trenches at hadal (>6,000 m) depths are hot spots of organic matter deposition and mineralization and can host abundant and active bacterial assemblages. However, the factors able to shape their biodiversity and functioning remain largely unexplored, especially in subsurface sediments. Here, we investigated the patterns and drivers of benthic bacterial α- and β-diversity (i.e., OTU richness and turnover diversity) along the vertical profile down to 1.5 m sediment depth in the Izu-Bonin Trench (at ~10,000 m water depth). The protease and glucosidase enzymatic activity rates were also determined, as a proxy of organic matter degradation potential in the different sediment layers. Molecular fingerprinting based on automated ribosomal intergenic spacer analysis (ARISA) indicated that the α-diversity of bacterial assemblages remained high throughout the vertical profile, and that the turnover (β-) diversity among sediment horizons reached values up to 90% of dissimilarity. Multivariate distance-based linear modelling (DISTLM) pointed out that the diversity and functioning of the hadal bacterial assemblages were influenced by the variability of environmental conditions (including the availability of organic resources and electron donors/acceptors) and of viral production rates along the sediment vertical profile. Based on our results we can argue that the heterogeneity of physical-chemical features of the hadal sediments of the Izu-Bonin Trench contribute to increase the niches availability for different bacterial taxa, while viruses contribute to maintain high levels of bacterial turnover diversity and to enhance organic matter cycling in these extremely remote and isolated ecosystems.